Occurrence and Diversity of Intestinal Parasites on Raw Vegetables Sold in Samaru, Zaria - Ocholi Yahaya; Henry Ganriel Bishop; Hauwa Abubakar; Samuel Jacob; Christiana Ozeiza Apata (UMYU Journal of Microbiology Research)
Vegetables are part of everyday diet.  There has been more emphasis on their palatability and nutritional values, but they potentially contribute to transmitting intestinal parasites, among other pathogens, to man.  This study examined 10 samples of five commonly consumed vegetables from Samaru in Zaria, Nigeria.  Twenty-five (25g) fresh vegetable samples were washed in 225 mL of sterile normal saline and gently shaken for 60 seconds.  The wash water was allowed to stay for 3 hr in the dark.  The supernatant was carefully discarded until only about 15mL was left.  The sediment was further concentrated by centrifuging at 3000 revolutions per minute for 5 minutes and examined for intestinal parasites on wet mounts using the compound light microscope.  The overall occurrence of intestinal parasites on the vegetables was 22.0%.  Ascaris lumbricoides was the most occurring parasite (18.0%), followed by equal 2.0% of hookworms, Trichuris trichiura and Fasciola species.  Vegetable samples obtained from Mangorori Market had the highest contamination with Ascaris lumbricoides than other markets, but overall parasitic contamination was highest on vegetables obtained from ABU Community Market.  Cabbage was the most contaminated (50.0%), followed by 20% each of lettuce and carrots.  Samples displayed on mats during the sale had the highest contamination with Ascaris lumbricoides (23.5%), followed by those displayed on the ground (22.2%).  There was higher intestinal parasitic contamination of vegetables sold in dirty surroundings (23.3%) than in relatively clean surroundings (10.0%).  Sufficient orientation on the role of fresh raw vegetables in transmitting intestinal parasites should be aimed at farmers, sellers, distributors and final consumers to curb potential health risks